Escalation of Growth and Yield in Mungbean by Sink Manipulation: An Approach for Minimizing Pod Picking Episode (Bangladesh Agronomy Journal, 2023)
Farmers’ frequently experience difficulties with their mungbean (indeterminate type) crops harvests due to continuous picking that prolong the pod-picking episode and cause an economic crisis. To solve these issues, deflowering strategies (sink manipulation) were employed in this study following the randomized complete block design. A series of deflowering strategies were started from 40 days after sowing (DAS) to 55 DAS; resulting reduced pod production as well as pod picking episode (3 to 4 times) with 6.8-36.8% seed yield compared to control. The minimum seed yield reduction was 6.8%; deflowering at 55 DAS; with the maximum gross margin Tk.112,800 ha−1. Considering relative yield, yield reduction, and gross margin, 50 or 55 days produced flower (which would be matured within 60-65 DAS) could be considered for obtaining the economic seed yield.Bangladesh Agron. J. 2023, 26(1): 48-55